Designing a research experience for teachers: applying features of effective professional development to a hybrid setting. Issue 4 (8th August 2022) - Wakefield, Wendy
ABSTRACT: To facilitate transfer of teachers' learning into classroom practice, science and engineering teacher professional development (PD) experiences should increase teachers' content knowledge, disciplinary practices, and pedagogical strategies. As this can be difficult within traditional PD contexts, this study is a qualitative investigation of hybrid PD program design. The author explores influences on five teachers' learning and instruction when seven features of effective PD, derived mainly from traditional PD, were integrated into both the pedagogical and practice components of a hybrid Research Experience for Teachers (RET) PD. Through constant comparative analysis of interviews, reflections, artifacts, and classroom observations, the author discovered that explicit connections between the seven features across pedagogical and disciplinary aspects of the RET facilitated teachers transferring their learning into classroom practices in ways applicable to their specific contexts. Thus, these seven features of effective PD hold promise as an organizing framework for designing and evaluating a hybrid PD.